FloNa: Children Educational App for Indonesian Endangered Species Based on Augmented Reality - Amir Hasanudin Fauzi; Rahmadi Wijaya; Alfian Ghazali; Endra Wahyu Wardana; Ageng Prasetio; Neca Aqila (IJAIT (International Journal of Applied Information Technology), 2020)
Indonesia has an enormous number of endangered species of flora (plants) as well as fauna (animals). Several factors influence endangered species such as lack of early education in this problem. Whereas, children, especially in school ages, have the most potential role in the future to solve this problem. To influence the behavior and attitudes of children towards wildlife, Conservation Education is the solution. By providing appropriate and effective conservation education, future conservation behavior can change in a positive direction. To address this opportunity, we proposed FloNa, a mobile app to educate children about Indonesian endangered species. FloNa is empowered by augmented reality to help children imagine and observe the real form of endangered plants and animals. Furthermore, we conducted experiments to analyze the efficiency of this app to overcome this problem. The alpha testing result shows that FloNa has a robust design and implementation. Moreover, from the beta testing result, we could conclude that FloNa could significantly support and promote endangered species conservation education for children in Indonesia.